A nomogram for predicting mortality risk in geriatric patients with hip fractures complicated by pneumonia: A multicenter study - Kaiming Zhang; Xiangwei Li; Yujia Xiao; Cheng Zhou; Yu Liu; Fan Zhen; Hao Zhang; Mao Nie (SAGE Open Medicine)
Objectives: Pneumonia is a common perioperative complication in geriatric patients with hip fractures. This study aimed to analyze demographic characteristics, mortality rates, postoperative outcomes, and perioperative comorbidities, identify risk factors for mortality, and develop a nomogram for predicting the prognosis of these patients. Methods: Data on patients hospitalized for arthroplasty for hip fractures from 2020 to 2023 at three hospitals were retrospectively analyzed. Patients were divided into the P group (patients with hip fractures complicated with pneumonia) and the C group (patients with hip fractures without pneumonia) and demographic characteristics, mortality, postoperative outcomes, and perioperative comorbidities of the patients were analyzed. Multiple logistic regression was then used to identify independent risk factors for inpatient mortality in the P group and a nomogram was constructed to predict inpatient mortality. The predictive performance of the nomogram was assessed using receiver operating characteristic curves, decision curve analysis, and calibration curves. Results: A total of 311 patients participated in the study. Patients in the P group had longer hospitalization ( p = 0.001), higher inpatient mortality ( p < 0.001), higher mortality (30 days) ( p < 0.001), and a poorer recovery of hip function ( p < 0.001). Multiple logistic regression showed that age, BMI, total hip arthroplasty, diabetes, and chronic obstructive pulmonary disease were independent risk factors for inpatient mortality in the P group; these factors were incorporated in the nomogram. The C-index of the nomogram was 0.868 (95% CI: 0.802–0.933), and the C-index of internal bootstrapping validation was 0.851 (95% CI: 0.793–0.908), indicating the effectiveness of the nomogram in predicting patient prognosis. Conclusions: Coinfection with pneumonia adversely affected both recovery of hip function and survival in geriatric patients with hip fractures. Age, BMI, total hip arthroplasty, diabetes, and chronic obstructive pulmonary disease were found to be independent risk factors for mortality in this patient population.